(Meth) Acrylic Resin Particles, Carrier Composition, Slurry Composition, And Method For Producing Electronic Component

By using characteristic methacrylic resin particles and optimized carrier composition, poor dispersion and oxidation problems in the prior art are solved, high dispersion and low temperature decomposition are achieved, and reliability of laminated ceramic capacitors is improved.

CN119213040APending Publication Date: 2024-12-27SEKISUI CHEMICAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380027324.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-30
Filing Date
2023-08-17
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

In the prior art, the high decomposition temperature of polyvinyl acetal resin cannot be suitable for low-temperature firing. The acrylic resin has poor dispersion when using fine inorganic particles and is prone to oxidation at high firing temperatures, resulting in the reliability of laminated ceramic capacitors. and electrical characteristics are reduced.

Method used

A with a weight average molecular weight between 100,000 and 1 million, S atom concentration between 0.03% and 2.50%, COOH group concentration between 0.06% and 3.00%, K atom concentration between 0.010% and 1.000% As a binder, acrylic resin particles combine specific carrier compositions and slurry compositions to form high dispersion and high viscosity inorganic particle dispersion slurry through the optimization of solvents and dispersants, and are used to make laminated ceramic capacitors. External electrode.

Benefits of technology

The dispersion of inorganic particles with excellent low-temperature decomposition is achieved, and the oxidation of inorganic particles such as copper is prevented, the dispersion of inorganic particles and the reliability of laminated ceramic capacitors is improved, and high-quality electronic components are ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005040760090000291
    Figure BDA0005040760090000291
  • Figure BDA0005040760090000301
    Figure BDA0005040760090000301
  • Figure BDA0005040760090000311
    Figure BDA0005040760090000311
Patent Text Reader

Abstract

Provided are (meth) acrylic resin particles which have excellent low-temperature degradability, are capable of preventing deterioration caused by oxidation of inorganic particles such as copper when used as a binder for dispersing inorganic particles, and are capable of producing an inorganic particle dispersed slurry composition which has particularly excellent dispersibility of fine inorganic particles. Furthermore, provided are (meth) acrylic resin particles which, in particular, can be used as a binder for an external electrode of a laminated ceramic capacitor, thereby making it possible to produce a laminated ceramic capacitor having excellent reliability. Further, a carrier composition, a paste composition, and a method for manufacturing an electronic component are provided. This (meth) acrylic resin particle has a weight-average molecular weight of 100,000 to 1,000,000 (inclusive) and an S atom weight concentration of 0.03 wt% to 2.50 wt% (inclusive).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to (meth)acrylic resin particles, a carrier composition, a slurry composition, and a method for producing an electronic component. Background Art

[0002] A known multilayer ceramic capacitor comprises a laminated body composed of a plurality of alternately stacked dielectric layers and internal electrodes, and a pair of external electrodes sandwiching the laminated body. The external electrodes are formed by applying a conductive paste for external electrodes to the surface of the laminated body and sintering the paste.

[0003] In recent years, with the miniaturization of multilayer ceramic capacitors, the miniaturization of inorganic particles used in external electrodes has also advanced. Miniaturized inorganic particles tend to aggregate in the paste. Agglomeration can leave gaps during the degreasing and firing processes, reducing the dispersibility of the inorganic particles in the finished multilayer ceramic capacitor, ultimately degrading the electrical properties of the product.

[0004] Ethyl cellulose is commonly used as a binder resin for external electrodes. For example, Patent Document 1 discloses a method for effectively dispersing ceramic powder in a structure using such a binder. Specifically, the method discloses a method in which ceramic powder, such as calcium titanate, is crushed in a solvent such as ethanol and then a resin, such as polyvinyl butyral resin or ethyl cellulose resin, is added.

[0005] In addition, Patent Document 2 discloses a method of using an acrylic resin or the like as a binder.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Laid-Open No. 2011-84433

[0009] Patent Document 2: Japanese Patent Application Laid-Open No. 2021-111525 Summary of the Invention

[0010] Problems to be solved by the invention

[0011] However, the polyvinyl acetal resin described in Patent Document 1 has a problem in that its decomposition temperature is high and it cannot be used for applications requiring low-temperature firing, such as applications using easily oxidizable metals such as copper or low-melting-point glass.

[0012] Patent Document 2 describes the use of an acrylic resin, but the use of fine inorganic particles with an average particle size of less than 1 μm leads to poor dispersibility. Furthermore, the acrylic resin described in Patent Document 2 suffers from degradation due to oxidation during degreasing, which requires high calcination temperatures.

[0013] The present invention aims to provide (meth)acrylic resin particles having excellent low-temperature decomposition properties. When used as a binder for dispersing inorganic particles, these particles can prevent degradation caused by oxidation of inorganic particles such as copper, thereby enabling the production of an inorganic particle-dispersed slurry composition having particularly excellent dispersibility of fine inorganic particles. Furthermore, the present invention aims to provide (meth)acrylic resin particles that, particularly when used as a binder for external electrodes of a multilayer ceramic capacitor, can produce a multilayer ceramic capacitor having excellent reliability. Furthermore, the present invention aims to provide a vehicle composition, a slurry composition, and a method for producing an electronic component.

[0014] Means for solving problems

[0015] The present invention (1) relates to (meth)acrylic resin particles having a weight average molecular weight of 100,000 to 1,000,000 and a S atom weight concentration of 0.03% to 2.50% by weight.

[0016] The present invention (2) relates to the (meth)acrylic resin particles of the present invention (1), wherein the weight concentration of the COOH group is 0.06% by weight or more and 3.00% by weight or less.

[0017] The present invention (3) relates to the (meth)acrylic resin particles of the present invention (1) or (2), wherein the weight concentration of K atoms is 0.010 wt% or more and 1.000 wt% or less.

[0018] The present invention (4) relates to (meth)acrylic resin particles comprising any combination of any of the present inventions (1) to (3), wherein the content of a component derived from an acrylic monomer is 5% by weight or less.

[0019] The present invention (5) relates to (meth)acrylic resin particles comprising any combination of any of the present inventions (1) to (4), wherein the average particle size is 0.1 μm or more and 1.0 μm or less.

[0020] The present invention (6) relates to a carrier composition comprising the (meth)acrylic resin particles according to any one of the present inventions (1) to (5) and a solvent including an organic solvent.

[0021] The present invention (7) relates to the carrier composition of the present invention (6), wherein the solvent further contains 100 ppm by weight or more and 40,000 ppm by weight or less of water.

[0022] The present invention (8) relates to the carrier composition of the present invention (6) or (7), wherein the organic solvent contains a compound having two or more OH groups, and the content of the above-mentioned compound having two or more OH groups in the solvent is greater than 10 weight % and less than 50 weight %.

[0023] The present invention (9) relates to a slurry composition comprising the carrier composition according to any one of the present inventions (6) to (8), inorganic particles, and a dispersant.

[0024] The present invention (10) relates to a method for producing an electronic component, which uses the slurry composition of the present invention (9).

[0025] Hereinafter, the present invention will be described in detail.

[0026] The present inventors have discovered that (meth)acrylic resin particles having a predetermined weight-average molecular weight and a predetermined weight concentration of sulfur atoms exhibit excellent low-temperature decomposition properties and, when used as a binder for dispersing inorganic particles, can prevent degradation caused by oxidation of inorganic particles such as copper. Furthermore, the present inventors have discovered that the use of such (meth)acrylic resins enables the production of inorganic particle-dispersed slurry compositions having particularly excellent dispersibility of fine inorganic particles. Furthermore, the present inventors have discovered that the use of such (meth)acrylic resin particles as a binder for external electrodes of multilayer ceramic capacitors enables the production of highly reliable multilayer ceramic capacitors, thereby completing the present invention.

[0027] The weight average molecular weight (Mw) of the (meth)acrylic resin particles is 100,000 to 1,000,000.

[0028] By setting the above range, the dispersibility of the inorganic particles can be improved when the inorganic particle-dispersed slurry composition is prepared, and the sufficient viscosity can be provided to improve the printability.

[0029] The weight average molecular weight (Mw) is preferably 150,000 or more, particularly preferably 170,000 or more. Furthermore, the weight average molecular weight (Mw) is preferably 900,000 or less, more preferably 800,000 or less, further preferably 700,000 or less, and particularly preferably 500,000 or less.

[0030] The (meth)acrylic resin particles preferably have a ratio (Mw / Mn) of weight average molecular weight (Mw) to number average molecular weight (Mn) of 8 or less, more preferably 6 or less, and even more preferably 5 or less.

[0031] The weight average molecular weight (Mw) and the number average molecular weight (Mn) are average molecular weights based on polystyrene conversion and can be obtained by GPC measurement using, for example, a column LF-804 (manufactured by Showa Denko K.K.) as a column.

[0032] The weight concentration of S atoms contained in the (meth)acrylic resin particles is 0.03% by weight or more and 2.50% by weight or less.

[0033] By setting it as the said range, when making into the inorganic particle dispersion slurry composition, the dispersibility of an inorganic particle can be made especially excellent.

[0034] The weight concentration of the S atoms is preferably 0.30 wt% or more, preferably 2.00 wt% or less, more preferably 0.50 wt% or more, more preferably 1.80 wt% or less, further preferably 0.70 wt% or more, further preferably 1.50 wt% or less.

[0035] The weight concentration of S atoms refers to the ratio of the weight of S atoms in the (meth)acrylic resin structure to the weight of the (meth)acrylic resin particles, and can be calculated based on the following formula. The above values ​​are rounded to the third decimal place.

[0036] Weight concentration of S atoms contained in (meth)acrylic resin particles=[(weight of S atoms contained in all monomers+weight of S atoms contained in all chain transfer agents+weight of S atoms contained in all polymerization initiators) / (weight of all monomers+weight of all chain transfer agents+weight of all polymerization initiators)]×100

[0037] The weight concentration of the S atoms can also be determined by ICP-AES (Inductively Coupled Plasma Atomic Emission Spectrometry).

[0038] The weight concentration of the COOH groups contained in the (meth)acrylic resin particles is preferably 0.06% by weight or more and preferably 3.00% by weight or less.

[0039] When the content is within the above range, there is an advantage in that the dispersibility of the inorganic particles can be made particularly excellent.

[0040] The weight concentration of the COOH groups is more preferably 0.50 wt% or more, more preferably 2.70 wt% or less, further preferably 1.00 wt% or more, and further preferably 2.50 wt% or more.

[0041] The weight concentration of COOH groups refers to the ratio of the weight of COOH groups in the (meth)acrylic resin structure to the weight of the (meth)acrylic resin particles, and can be calculated based on the following formula: The above values ​​are rounded to the third decimal place.

[0042] Weight concentration of COOH groups contained in (meth)acrylic resin particles=[(weight of COOH groups contained in all monomers+weight of COOH groups contained in all chain transfer agents+weight of COOH groups contained in all polymerization initiators) / (weight of all monomers+weight of all chain transfer agents+weight of all polymerization initiators)]×100

[0043] The weight concentration of the COOH groups can also be determined by ESCA analysis using a gas phase chemical modification method.

[0044] The weight concentration of K atoms contained in the (meth)acrylic resin particles is preferably 0.001% by weight or more and preferably 1.500% by weight or less.

[0045] By setting it as the said range, storage stability improves.

[0046] The weight concentration of K atoms is more preferably 0.005 wt % or more, and more preferably 1.200 wt % or less.

[0047] The weight concentration of K atoms is the ratio of the weight of K atoms in the (meth)acrylic resin structure to the weight of the (meth)acrylic resin particles, and can be calculated based on the following formula: The above values ​​are rounded to the fourth decimal place.

[0048] Weight concentration of K atoms contained in (meth)acrylic resin particles=[(weight of K atoms contained in all monomers+weight of K atoms contained in all chain transfer agents+weight of K atoms contained in all polymerization initiators) / (weight of all monomers+weight of all chain transfer agents+weight of all polymerization initiators)]×100

[0049] In addition, the weight concentration of the K atoms can also be measured using an atomic absorption spectrophotometer.

[0050] The weight concentration of OH groups contained in the (meth)acrylic resin particles is preferably 0.05% by weight or more, preferably 3.00% by weight or less, more preferably 0.08% by weight or more, more preferably 2.50% by weight or less, further preferably 0.10% by weight or more, and further preferably 2.00% by weight or less. Within this range, storage stability, viscosity stability, and decomposability are improved.

[0051] The weight concentration of OH groups refers to the ratio of the weight of OH groups in the (meth)acrylic resin structure to the weight of the (meth)acrylic resin particles, and can be calculated based on the following formula: The above values ​​are rounded off to the third decimal place.

[0052] Weight concentration of OH groups contained in (meth)acrylic resin particles=[(weight of OH groups contained in all monomers+weight of OH groups contained in all chain transfer agents+weight of OH groups contained in all polymerization initiators) / (weight of all monomers+weight of all chain transfer agents+weight of all polymerization initiators)]×100

[0053] The weight concentration of the OH groups can also be determined by ESCA analysis using a gas phase chemical modification method.

[0054] The ratio of the weight concentration of COOH groups to the weight concentration of S atoms in the (meth)acrylic resin particles (weight concentration of COOH groups / weight concentration of S atoms) is preferably 0.03 or more and preferably 3.00 or less, more preferably 0.05 or more and more preferably 1.00 or less.

[0055] The ratio of the weight concentration of OH groups to the weight concentration of S atoms in the (meth)acrylic resin particles (weight concentration of OH groups / weight concentration of S atoms) is preferably 0.10 or more and 3.00 or less, more preferably 0.15 or more and more preferably 1.20 or less.

[0056] The ratio of the weight concentration of K atoms to the weight concentration of S atoms contained in the (meth)acrylic resin particles (weight concentration of K atoms / weight concentration of S atoms) is preferably 0.01 or more and 1.50 or less, more preferably 0.05 or more and more preferably 1.20 or less.

[0057] The average particle size of the (meth)acrylic resin particles is preferably 0.1 μm or more and preferably 1.0 μm or less.

[0058] By setting it as the said range, the solubility of (meth)acrylic resin particles can be further improved.

[0059] The average particle size is more preferably 0.2 μm or more, more preferably 0.9 μm or less, further preferably 0.3 μm or more, and further preferably 0.8 μm or less.

[0060] The average particle size can be determined, for example, by measuring the volume average particle size using a laser diffraction / scattering particle size distribution analyzer.

[0061] The average particle size can be adjusted by adjusting the amount of the polymerization initiator. For example, a higher content of the polymerization initiator tends to result in a smaller average particle size, while a lower content tends to result in a larger average particle size.

[0062] The (meth)acrylic resin particles preferably contain a segment derived from a (meth)acrylate having 8 or less carbon atoms in an ester substituent.

[0063] The fact that the ester substituent has 8 or less carbon atoms means that the total number of carbon atoms in the (meth)acrylate other than the carbon atoms constituting the (meth)acryloyl group is 8 or less. In this specification, the (meth)acrylate having 8 or less carbon atoms in the ester substituent refers to a (meth)acrylate other than a (meth)acrylate having a glycidyl group described below.

[0064] Examples of the (meth)acrylate having an ester substituent with 8 or less carbon atoms include (meth)acrylates having a linear, branched, or cyclic alkyl group.

[0065] Examples of the (meth)acrylate having a linear alkyl group include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, and n-butyl (meth)acrylate.

[0066] Examples of the (meth)acrylate having a branched alkyl group include isopropyl (meth)acrylate, t-butyl (meth)acrylate, isobutyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate.

[0067] Examples of the (meth)acrylate having a cyclic alkyl group include cyclohexyl (meth)acrylate and benzyl (meth)acrylate.

[0068] In addition, as the (meth)acrylate having 8 or less carbon atoms in the ester substituent, (meth)acrylates having a hydroxyl group or a carboxyl group, such as 2-hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, and (meth)acrylic acid, can also be used.

[0069] Among them, (meth)acrylates having a linear alkyl group and (meth)acrylates having a branched alkyl group are preferred. Methyl methacrylate, ethyl methacrylate, and isobutyl methacrylate are more preferred. A combination of a (meth)acrylate having a linear alkyl group and a (meth)acrylate having a branched alkyl group is even more preferred.

[0070] As the (meth)acrylate having an ester substituent with 8 or less carbon atoms, a (meth)acrylate having an ester substituent with 1 to 4 carbon atoms or a (meth)acrylate having an ester substituent with 5 to 8 carbon atoms can be used. Among them, a (meth)acrylate having an ester substituent with 1 to 4 carbon atoms is preferred.

[0071] The content of the segments derived from the (meth)acrylate ester having 8 or fewer carbon atoms in the ester substituent in the (meth)acrylic resin particles is preferably 40% by weight or more, more preferably 60% by weight or more, and even more preferably 80% by weight or more. The upper limit is not particularly limited, but is preferably 100% by weight or less, more preferably 99% by weight or less, and even more preferably 98% by weight or less.

[0072] The content of the above-mentioned segment in the (meth)acrylic resin particles can be calculated based on the ratio of each monomer relative to 100 parts by weight of the raw material monomers excluding the polymerization initiator and the chain transfer agent in the raw materials for producing the (meth)acrylic resin constituting the (meth)acrylic resin particles.

[0073] The content of the segments derived from the (meth)acrylate ester having 1 to 4 carbon atoms in the ester substituent in the (meth)acrylic resin particles is preferably 40% by weight or more, more preferably 60% by weight or more, and even more preferably 80% by weight or more. The upper limit is not particularly limited, but is, for example, 100% by weight or less.

[0074] The content of the segment derived from the (meth)acrylate having 1 to 2 carbon atoms in the ester substituent in the (meth)acrylic resin particles is preferably 35 wt % or more, more preferably 40 wt % or more, and preferably 65 wt % or less, more preferably 60 wt % or less.

[0075] The content of the segments derived from the (meth)acrylate ester having 5 to 8 carbon atoms in the ester substituent in the (meth)acrylic resin particles is preferably 60% by weight or less, more preferably 40% by weight or less, and even more preferably 20% by weight or less. The lower limit is not particularly limited, but is, for example, 0% by weight or more.

[0076] The content of the segment derived from methyl methacrylate in the (meth)acrylic resin particles is preferably 30% by weight or more and 60% by weight or less, more preferably 35% by weight or more and more preferably 50% by weight or less.

[0077] The content of the segment derived from ethyl methacrylate in the (meth)acrylic resin particles is preferably 10% by weight or more and 30% by weight or less, more preferably 15% by weight or more and more preferably 25% by weight or less.

[0078] The content of the segment derived from isobutyl methacrylate in the (meth)acrylic resin particles is preferably 30% by weight or more and preferably 60% by weight or less, more preferably 35% by weight or less, and even more preferably 50% by weight or less.

[0079] The (meth)acrylic resin particles may have a segment derived from a (meth)acrylate having 9 or more carbon atoms in an ester substituent.

[0080] The number of carbon atoms in the ester substituent is more preferably 10 or more, preferably 30 or less, and more preferably 20 or less.

[0081] Examples of the (meth)acrylate having 9 or more carbon atoms in the ester substituent include (meth)acrylates having a linear or branched alkyl group having 9 or more carbon atoms and polyalkylene glycol (meth)acrylates.

[0082] Examples of the (meth)acrylate having a linear or branched alkyl group having 9 or more carbon atoms include n-nonyl (meth)acrylate, isononyl (meth)acrylate, n-decyl (meth)acrylate, isodecyl (meth)acrylate, n-lauryl (meth)acrylate, isolauryl (meth)acrylate, n-stearyl (meth)acrylate, and isostearyl (meth)acrylate.

[0083] Examples of the polyalkylene glycol (meth)acrylate include polyalkylene glycol (meth)acrylates having an ethylene glycol unit, a propylene glycol unit, a butylene glycol unit, and the like.

[0084] Furthermore, the polyalkylene glycol (meth)acrylate may have an alkoxy group at the terminal, or may have an ethylhexyl group at the terminal.

[0085] Furthermore, the polyalkylene glycol (meth)acrylate may have a linear alkylene glycol unit or a branched alkylene glycol unit.

[0086] The content of the segments derived from the (meth)acrylate ester having 9 or more carbon atoms in the ester substituent in the (meth)acrylic resin particles is preferably 60% by weight or less, more preferably 40% by weight or less, and even more preferably 20% by weight or less. The lower limit is not particularly limited, but is, for example, 0% by weight or more.

[0087] The (meth)acrylic resin particles may have a segment derived from (meth)acrylate having a glycidyl group.

[0088] Examples of the (meth)acrylate having a glycidyl group include glycidyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate glycidyl ether, and 3,4-epoxycyclohexyl (meth)acrylate.

[0089] The lower the content of the acrylic monomer-derived segments in the (meth)acrylic resin particles, the better the low-temperature decomposition resistance. Therefore, the content is preferably 5% by weight or less, more preferably 1% by weight or less. The lower limit is not particularly limited, and is, for example, 0% by weight or more.

[0090] It should be noted that the above-mentioned acrylic monomers refer to acrylic acid and acrylic acid esters.

[0091] The glass transition temperature (Tg) of the (meth)acrylic resin particles is preferably 30° C. or higher and preferably 85° C. or lower.

[0092] By setting it as the said range, the addition amount of a plasticizer can be reduced, and low-temperature decomposition property can be improved.

[0093] The Tg is more preferably 32°C or higher, more preferably 80°C or lower, further preferably 42°C or higher, and further preferably 75°C or lower.

[0094] In addition, the said glass transition temperature (Tg) can be measured using a differential scanning calorimeter (DSC) etc., for example.

[0095] The (meth)acrylic resin particles preferably have a 90% by weight decomposition temperature when heated from 30°C at 5°C / min of 280°C or lower, more preferably 270°C or lower, and even more preferably 260°C or lower. The lower limit is not particularly limited but is 30°C or higher, with a lower value being more preferred.

[0096] Examples of methods for producing the (meth)acrylic resin particles include a method in which an organic solvent or the like is added to a raw material monomer mixture containing a (meth)acrylate ester or the like to prepare a monomer mixed solution, a polymerization initiator and a chain transfer agent are further added to the obtained monomer mixed solution, and the raw material monomers are copolymerized.

[0097] The polymerization method is not particularly limited, and examples thereof include emulsion polymerization, suspension polymerization, bulk polymerization, interfacial polymerization, solution polymerization, etc. Among them, solution polymerization is preferred.

[0098] Examples of the organic solvent include toluene, ethyl acetate, butyl acetate, amyl acetate, hexyl acetate, ethyl butyrate, butyl butyrate, amyl butyrate, hexyl butyrate, isopropyl alcohol, methyl isobutyl ketone, methyl ethyl ketone, methyl isobutyl ketone, ethylene glycol ethyl ether, ethylene glycol monobutyl ether, ethylene glycol monoethyl ether acetate, diethylene glycol monoethyl ether, diethylene glycol monomethyl ether, diethylene glycol monoisobutyl ether, trimethylpentanediol monoisobutyrate, butyl carbitol, butyl carbitol acetate, terpineol, terpineol acetate, dihydroterpineol, dihydroterpineol acetate, Texanol, isophorone, butyl lactate, dioctyl phthalate, dioctyl adipate, benzyl alcohol, phenylpropylene glycol, and cresol. Among them, butyl acetate, terpineol, terpineol acetate, dihydroterpineol, dihydroterpineol acetate, diethylene glycol monoethyl ether, diethylene glycol monomethyl ether, diethylene glycol monoisobutyl ether, butyl carbitol, butyl carbitol acetate, and Texanol are preferred. Furthermore, butyl acetate, terpineol, terpineol acetate, dihydroterpineol, and dihydroterpineol acetate are more preferred. It should be noted that these organic solvents may be used alone or in combination of two or more.

[0099] Examples of the polymerization initiator include tert-butyl peroxypivalate, p-menthane hydroperoxide, diisopropylbenzene hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, isopropylbenzene hydroperoxide, tert-butyl hydroperoxide, cyclohexanone peroxide, and disuccinic acid peroxide. Examples include 2,2'-azobis[2-(2-imidazolin-2-yl)propane] dihydrochloride, 2,2'-azobis[2-(2-imidazolin-2-yl)propane] sulfate hydrate, acid mixtures of imidazole-based azo compounds such as 2,2'-azobis[2-(2-imidazolin-2-yl)propane], 2,2'-azobis(2-methylpropionamidine) dihydrochloride, and 2,2'-azobis[N- Water-soluble azo compounds such as [(2-carboxyethyl)-2-methylpropionamidine] tetrahydrate, 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)propionamide], and 4,4'-azobis-4-cyanovaleric acid; oxygen-containing acids such as potassium persulfate (potassium peroxodisulfate), ammonium persulfate (ammonium peroxodisulfate), and sodium persulfate (sodium peroxodisulfate); peroxides such as hydrogen peroxide, peracetic acid, performic acid, and perpropionic acid;

[0100] Among these, polymerization initiators containing S atoms and polymerization initiators containing K atoms are preferably used. Potassium persulfate, ammonium persulfate, 2,2'-azobis[2-(2-imidazolin-2-yl)propane] dihydrochloride, and 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)propionamide] are also preferred, with potassium persulfate and 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)propionamide] being more preferred.

[0101] The amount of the polymerization initiator added is preferably 0.03 parts by weight or more and 4.0 parts by weight or less, more preferably 0.05 parts by weight or more and more preferably 3.6 parts by weight or less, based on 100 parts by weight of the raw material monomers.

[0102] As the chain transfer agent, a chain transfer agent having a S atom is preferably used, and examples thereof include 3-mercapto-1,2-propanediol, 3-mercapto-1-propanol, 3-mercapto-2-butanol, 8-mercapto-1-octanol, 2-mercaptobenzimidazole, mercaptosuccinic acid, and thioglycolic acid.

[0103] Among them, 3-mercapto-1,2-propanediol and mercaptosuccinic acid are preferably used.

[0104] The amount of the chain transfer agent added is preferably 0.1 parts by weight or more and 10.0 parts by weight or less, more preferably 0.4 parts by weight or more and more preferably 5.0 parts by weight or less, based on 100 parts by weight of the raw material monomers.

[0105] The temperature during polymerization is preferably 50°C or higher and preferably 90°C or lower, more preferably 60°C or higher and more preferably 80°C or lower.

[0106] The carrier composition can be prepared using the (meth)acrylic resin particles and a solvent including an organic solvent.

[0107] The present invention also encompasses a carrier composition comprising the (meth)acrylic resin particles and a solvent including an organic solvent.

[0108] The content of the (meth)acrylic resin particles in the carrier composition is preferably 5% by weight or more and 30% by weight or less, more preferably 10% by weight or more and more preferably 20% by weight or less.

[0109] The above-mentioned carrier composition contains an organic solvent.

[0110] Examples of the organic solvent include alcohols such as aliphatic alcohols, glycols, terpene alcohols, and aromatic alcohols, aromatic hydrocarbons, esters, ketones, and N-methylpyrrolidone.

[0111] Examples of the aliphatic alcohols include ethanol, propanol, isopropanol, heptanol, octanol, decanol, tridecanol, lauryl alcohol, tetradecanol, cetyl alcohol, 2-ethyl-1-hexanol, octadecyl alcohol, hexadecanol, oleyl alcohol, Texanol, 2-butyl-2-ethyl-1,3-propanediol, and neopentyl glycol.

[0112] Examples of the diols include ethylene glycol monobutyl ether, diethylene glycol monoethyl ether, diethylene glycol monomethyl ether, diethylene glycol monoisobutyl ether, butyl carbitol, ethylene glycol monoethyl ether acetate, trimethylpentanediol monoisobutyrate, butyl carbitol acetate, Texanol, ethylene glycol monophenyl ether, propylene glycol monophenyl ether, and ethylene glycol ethyl ether.

[0113] Examples of the terpene alcohols include terpineol, dihydroterpineol, terpineol acetate, and dihydroterpineol acetate.

[0114] Examples of the aromatic alcohols include benzyl alcohol and the like.

[0115] Examples of the aromatic hydrocarbons include toluene and the like.

[0116] Examples of the esters include ethyl acetate, butyl acetate, hexyl acetate, isoamyl acetate, butyl butyrate, butyl lactate, dioctyl phthalate, and dioctyl adipate.

[0117] Examples of the ketones include methyl isobutyl ketone, methyl ethyl ketone, methyl isobutyl ketone, and isophorone.

[0118] Among them, aliphatic alcohols and terpene alcohols are preferred, and 2-butyl-2-ethyl-1,3-propanediol and dihydroterpineol acetate are more preferred.

[0119] The organic solvent preferably contains a compound having two or more OH groups.

[0120] The content of the compound having two or more OH groups in the solvent is preferably 10% by weight or more and preferably 50% by weight or less.

[0121] By setting it as the said range, there exists an advantage in that the dispersibility of an inorganic particle can be made particularly excellent.

[0122] The content of the solvent in the carrier composition is not particularly limited, but is preferably 65% ​​by weight or more and 90% by weight or less, more preferably 70% by weight or more and more preferably 85% by weight or less.

[0123] In the above-mentioned carrier composition, the solvent preferably further contains water.

[0124] The content of the water in the solvent is preferably 100 ppm by weight or more and preferably 40,000 ppm by weight or less.

[0125] By containing water in the above range, there are advantages in that the compatibility with the dispersant is improved and the thermal decomposition property is enhanced.

[0126] The content of the water in the solvent is more preferably 300 ppm by weight or more, and more preferably 20,000 ppm by weight or less.

[0127] The weight concentration of S atoms contained in the carrier composition is preferably 0.004 wt% or more and preferably 0.400 wt% or less, more preferably 0.100 wt% or more and more preferably 0.200 wt% or less.

[0128] The weight concentration of S atoms refers to the ratio of the weight of S atoms contained in the carrier composition to the weight of the entire carrier composition, and can be calculated based on the following formula.

[0129] Weight concentration of S atoms contained in the carrier composition = [content of (meth)acrylic resin particles in the carrier composition (wt%) × weight concentration of S atoms contained in (meth)acrylic resin particles (wt%)] ÷ 100

[0130] The weight concentration of the COOH groups contained in the carrier composition is preferably 0.005 wt% or more and preferably 0.500 wt% or less, more preferably 0.009 wt% or more and more preferably 0.300 wt% or less.

[0131] The weight concentration of COOH groups refers to the ratio of the weight of COOH groups contained in the carrier composition to the weight of the entire carrier composition, and can be calculated based on the following formula.

[0132] Weight concentration of COOH groups contained in the carrier composition = {[content of (meth)acrylic resin particles in the carrier composition (wt%) × weight concentration of COOH groups contained in the (meth)acrylic resin particles (wt%)] + [content of organic solvent in the carrier composition (wt%) × weight concentration of COOH groups contained in the organic solvent (wt%)]} ÷ 100

[0133] The weight concentration of OH groups contained in the carrier composition is preferably 0.01 wt% or more and preferably 13.00 wt% or less, more preferably 0.02 wt% or more and more preferably 11.00 wt% or less.

[0134] The weight concentration of OH groups refers to the ratio of the weight of OH groups contained in the carrier composition to the weight of the entire carrier composition, and can be calculated based on the following formula.

[0135] Weight concentration of OH groups contained in the carrier composition = {[content of (meth)acrylic resin particles in the carrier composition (wt%) × weight concentration of OH groups contained in the (meth)acrylic resin particles (wt%)] + [content of organic solvent in the carrier composition (wt%) × weight concentration of OH groups contained in the organic solvent (wt%)] + [content of water in the carrier composition (wt%) × weight concentration of OH groups in water (wt%)]} ÷ 100

[0136] The weight concentration of K atoms contained in the carrier composition is preferably 0.001 wt% or more and preferably 0.200 wt% or less, more preferably 0.010 wt% or more and more preferably 0.160 wt% or less.

[0137] The weight concentration of K atoms refers to the ratio of the weight of K atoms contained in the carrier composition to the weight of the entire carrier composition, and can be calculated based on the following formula.

[0138] Weight concentration of K atoms contained in the carrier composition = [content of (meth)acrylic resin particles in the carrier composition (wt%) × weight concentration of K atoms contained in (meth)acrylic resin particles (wt%)] ÷ 100

[0139] In addition, the ratio of the weight concentration of OH groups contained in the above-mentioned carrier composition to the weight concentration of S atoms (weight concentration of OH groups / weight concentration of S atoms) is preferably greater than 0.1, preferably less than 100, more preferably greater than 0.2, and more preferably less than 75.

[0140] Examples of a method for producing the carrier composition include a method of adding an organic solvent, water, or the like to the (meth)acrylic resin particles obtained by the above method and stirring and mixing the mixture.

[0141] The carrier composition, inorganic particles, and dispersant described above can be used to prepare a slurry composition.

[0142] A slurry composition containing the above-mentioned carrier composition, inorganic particles and a dispersant is also one of the present invention.

[0143] The content of the (meth)acrylic resin particles in the slurry composition is preferably 3% by weight or more and 10% by weight or less, more preferably 5% by weight or more and more preferably 8% by weight or less.

[0144] The content of the organic solvent in the slurry composition is preferably 25% by weight or more and preferably 40% by weight or less, more preferably 30% by weight or more and more preferably 35% by weight or less.

[0145] The water content in the slurry composition is preferably 30 ppm by weight or more, preferably 15,000 ppm by weight or less, more preferably 1,000 ppm by weight or more, more preferably 10,000 ppm by weight or less, further preferably 5,000 ppm by weight or more, further preferably 7,000 ppm by weight or less.

[0146] The slurry composition contains inorganic particles.

[0147] The inorganic particles are not particularly limited, and examples thereof include glass powder, ceramic powder, phosphor fine particles, silicon oxide, and metal fine particles.

[0148] The above-mentioned glass powder is not particularly limited, and examples thereof include: glass powders such as bismuth oxide glass, silicate glass, lead glass, zinc glass, boron glass, and glass powders of various silicon oxides such as CaO-Al2O3-SiO2 system, MgO-Al2O3-SiO2 system, and LiO2-Al2O3-SiO2 system.

[0149] In addition, as the above-mentioned glass powder, a SnO-B2O3-P2O5-Al2O3 mixture, a PbO-B2O3-SiO2 mixture, a BaO-ZnO-B2O3-SiO2 mixture, a ZnO-Bi2O3-B2O3-SiO2 mixture, a Bi2O3-B2O3-BaO-CuO mixture, a Bi2O3-ZnO-B2O3-Al2O3-SrO mixture, a ZnO-Bi2O3-B2O3 mixture, a Bi2O3-SiO2 mixture, a P2O5-Na2O-CaO-BaO-Al2O3-B2O3 mixture, a P2O5-SnO mixture, a P2O5-SnO-B2O3 mixture, or a P2O5-SnO-B2O3 mixture can also be used. Glass powders include a mixture of P2O5-SnO-SiO2, a CuO-P2O5-RO mixture, a SiO2-B2O3-ZnO-Na2O-Li2O-NaF-V2O5 mixture, a P2O5-ZnO-SnO-R2O-RO mixture, a B2O3-SiO2-ZnO mixture, a B2O3-SiO2-Al2O3-ZrO2 mixture, a SiO2-B2O3-ZnO-R2O-RO mixture, a SiO2-B2O3-Al2O3-RO-R2O mixture, a SrO-ZnO-P2O5 mixture, a SrO-ZnO-P2O5 mixture, and a BaO-ZnO-B2O3-SiO2 mixture. It should be noted that R is an element selected from the group consisting of Zn, Ba, Ca, Mg, Sr, Sn, Ni, Fe, and Mn.

[0150] Glass powders that are particularly preferably PbO-B2O3-SiO2 mixtures, lead-free glass powders such as BaO-ZnO-B2O3-SiO2 mixtures or ZnO-Bi2O3-B2O3-SiO2 mixtures without lead.

[0151] The above ceramic powders are not particularly limited. For example, they include: alumina, ferrite, zirconia, zircon, barium zirconate, calcium zirconate, titanium oxide, barium titanate, strontium titanate, calcium titanate, magnesium titanate, zinc titanate, lanthanum titanate, neodymium titanate, lead zirconate titanate (Japanese: チタン酸ジルコン鉛), aluminum nitride (Japanese: 窒化アルミナ), silicon nitride, boron nitride, boron carbide, barium stannate, calcium stannate, magnesium silicate, mullite, steatite, cordierite, forsterite, etc.

[0152] In addition, ITO, FTO, niobium oxide, vanadium oxide, tungsten oxide, strontium lanthanum manganite (Japanese: ランタンストロンチウムマンガナイト), lanthanum strontium cobalt ferrite (Japanese: ランタンストロンチウムコバルトフェライト), yttrium-stabilized zirconia, gadolinium-doped ceria, nickel oxide, lanthanum chromate, etc. can also be used.

[0153] The above phosphor particles are not particularly limited. For example, as the phosphor substances, blue phosphor substances, red phosphor substances, green phosphor substances, etc. that are known as phosphor substances for displays in the past can be used. As the blue phosphor substances, for example, MgAl 10 O 17 : Eu series, Y2SiO5:Ce series, CaWO4:Pb series, BaMgAl 14 O 23 : Eu series, BaMgAl 16 O 27 : Eu series, BaMg2Al 14 O 23 : Eu series, BaMg2Al 14 O 27 : Eu series, ZnS:(Ag,Cd) series substances. As the red phosphor substances, for example, Y2O3:Eu series, Y2SiO5:Eu series, Y3Al5O 12 : Eu series, Zn3(PO4)2:Mn series, YBO3:Eu series, (Y,Gd)BO3:Eu series, GdBO3:Eu series, ScBO3:Eu series, LuBO3:Eu series substances. As the green phosphor substances, for example, Zn2SiO4:Mn series, BaAl 12 O 19 : Mn series, SrAl 13 O 19 : Mn series, CaAl 12 O 19:Mn series, YBO3:Tb series, BaMgAl 14 O 23 : Mn series, LuBO3: Tb series, GdBO3: Tb series, ScBO3: Tb series, Sr6Si3O3Cl4: Eu series. In addition, ZnO: Zn series, ZnS: (Cu, Al) series, ZnS: Ag series, Y2O2S: Eu series, ZnS: Zn series, (Y, Cd)BO3: Eu series, BaMgAl 12 O 23 : Eu series substances.

[0154] The metal fine particles are not particularly limited, and examples thereof include powders containing iron, copper, nickel, palladium, platinum, gold, silver, aluminum, tungsten, and alloys thereof.

[0155] In addition, metals such as copper and iron that have good adsorption characteristics with carboxyl groups, amino groups, amide groups, etc. and are easily oxidized can also be suitably used. These metal powders can be used alone or in combination of two or more.

[0156] Furthermore, as the metal fine particles, in addition to the metal complexes, various carbon blacks, carbon nanotubes, and the like can also be used.

[0157] The inorganic particles preferably contain lithium or titanium. Specifically, for example, low melting point glass such as LiO2-Al2O3-SiO2 inorganic glass, Li2S-M x S y (M=B, Si, Ge, P) and other lithium chalcogenide glasses, lithium cobalt composite oxides such as LiCeO2, lithium manganese composite oxides such as LiMnO4, lithium nickel composite oxides, lithium vanadium composite oxides, lithium zirconium composite oxides, lithium hafnium composite oxides, lithium silicophosphate (Li 3.5 Si 0.5 P 0.5 O4), lithium titanium phosphate (LiTi2(PO4)3), lithium titanate (Li4Ti5O 12 )、Li 4 / 3 Ti 5 / 3O4, LiCoO2, lithium germanium phosphate (LiGe2(PO4)3), Li2-SiS glass, Li4GeS4-Li3PS4 glass, LiSiO3, LiMn2O4, Li2S-P2S5 glass·ceramics, Li2O-SiO2, Li2O-V2O5-SiO2, LiS-SiS2-Li4SiO4 glass, LiPON and other ion conductive oxides, Li2O-P2O5-B2O3, Li2O-GeO2Ba and other lithium oxide compounds, Li x Al y Ti z (PO4)3 series glass, Lax Li y TiO z Glass, Li x Ge y P z O4 glass, Li7La3Zr2O 12 Glass, Li v Si w P x S y Cl z Glass, lithium niobium oxides such as LiNbO3, lithium aluminum oxide compounds such as Li-β-alumina, Li 14 Lithium zinc oxides such as Zn(GeO4)4, etc.

[0158] The average particle size of the inorganic particles is preferably 0.01 μm or more and preferably 5 μm or less, more preferably 0.05 μm or more and more preferably 3 μm or less, further preferably 0.1 μm or more and further preferably 1 μm or less.

[0159] The average particle size can be determined, for example, by measuring the volume average particle size using a laser diffraction / scattering particle size distribution analyzer.

[0160] The content of the inorganic particles in the slurry composition is preferably 30% by weight or more and preferably 90% by weight or less. Within the above range, the slurry composition can have sufficient viscosity, excellent coating properties, and excellent dispersibility of the inorganic particles.

[0161] The content of the inorganic particles is more preferably 40% by weight or more, and more preferably 70% by weight or less.

[0162] The slurry composition contains a dispersant.

[0163] As the dispersant, for example, fatty acids, aliphatic amines, alkanolamides, and phosphoric acid esters are suitable. In addition, a silane coupling agent or the like may be added.

[0164] The fatty acid is not particularly limited, and examples thereof include saturated fatty acids such as behenic acid, stearic acid, palmitic acid, myristic acid, lauric acid, capric acid, caprylic acid, and coconut oil fatty acid; and unsaturated fatty acids such as oleic acid, linoleic acid, linolenic acid, sorbic acid, tallow fatty acid, and hydrogenated castor oil fatty acid (Japanese: himasi hardened fatty acid). Among them, lauric acid, stearic acid, and oleic acid are suitable.

[0165] The aliphatic amine is not particularly limited, and examples thereof include laurylamine, myristylamine, cetylamine, stearylamine, oleylamine, alkyl(coconut)amine (Japanese: アルキル(ヤシ)アミン), alkyl(hydrogenated tallow)amine, alkyl(tallow)amine, and alkyl(soy)amine.

[0166] The alkanolamide is not particularly limited, and examples thereof include coconut oil fatty acid diethanolamide, tallow fatty acid diethanolamide, lauric acid diethanolamide, and oleic acid diethanolamide.

[0167] The phosphate ester is not particularly limited, and examples thereof include polyoxyethylene alkyl ether phosphate and polyoxyethylene alkyl allyl ether phosphate.

[0168] The content of the dispersant in the slurry composition is preferably 0.1% by weight or more and preferably 1% by weight or less, more preferably 0.15% by weight or more and more preferably 0.5% by weight or less.

[0169] The slurry composition may further contain additives such as a plasticizer and a surfactant.

[0170] Examples of the plasticizer include di(butoxyethyl) adipate, dibutoxyethoxyethyl adipate, triethyl glycol dibutyl ether, triethylene glycol bis(2-ethylhexanoate), triethylene glycol dicaproate, acetyl triethyl citrate, acetyl tributyl citrate, acetyl diethyl citrate, acetyl dibutyl citrate, dibutyl sebacate, triacetin, diethyl acetoxymalonate, and diethyl ethoxymalonate.

[0171] The surfactant is not particularly limited, and examples thereof include cationic surfactants, anionic surfactants, and nonionic surfactants.

[0172] The above-mentioned nonionic surfactant is not particularly limited, but is preferably a nonionic surfactant with an HLB value of 10 or more and 20 or less. Here, the HLB value is used as an indicator of the hydrophilicity and lipophilicity of the surfactant. Several calculation methods have been proposed. For example, with respect to ester-based surfactants, there are definitions such as setting the saponification value to S, setting the acid value of the fatty acid constituting the surfactant to A, and setting the HLB value to 20 (1-S / A). Specifically, nonionic surfactants having polyethylene oxide with an alkylene ether added to the fatty chain are suitable. Specifically, for example, polyoxyethylene lauryl ether and polyoxyethylene cetyl ether are suitable. It should be noted that the above-mentioned nonionic surfactants have good thermal decomposition properties, but if added in large quantities, the thermal decomposition properties of the inorganic particle dispersion slurry composition may be reduced. Therefore, the preferred upper limit of the content is 5% by weight.

[0173] The viscosity of the slurry composition of the present invention is not particularly limited, but is preferably 80,000 or more and 2,000,000 or less, more preferably 100,000 or more and more preferably 600,000 or less when measured at 25°C using a Brookfield viscometer.

[0174] By setting the above range, the obtained inorganic particle dispersion sheet can maintain a predetermined shape after coating by die printing etc. In addition, it can prevent problems such as the coating marks of the die not disappearing, thereby achieving excellent printability.

[0175] The method for preparing the slurry composition is not particularly limited, and conventionally known stirring methods may be used. Specifically, for example, a method in which the carrier composition, the inorganic particles, the dispersant, and other components such as additional solvents and plasticizers added as needed are stirred using a three-roll mill or the like may be used. The order of adding the components of the slurry composition may be appropriately set.

[0176] By using the above-mentioned slurry composition, an electronic component can be produced.

[0177] A method for producing an electronic component using the slurry composition is also one aspect of the present invention.

[0178] Examples of these electronic components include die attach pastes (ACPs), die attach films (ACFs), via electrodes for TSVs and TGVs, various circuits for touch panels, RFIDs, and sensor substrates, various die bonding agents, sealants for MEMS devices, and electrode materials for solar cells, multilayer ceramic capacitors, LTCCs, silicon capacitors, and all-solid-state batteries. In addition to the aforementioned electrode circuit applications, these materials can also be used for antimicrobial components, electromagnetic wave shielding, catalysts, and fluorescent materials.

[0179] For example, the inorganic particle-dispersed molded product can be produced by applying the slurry composition onto a support film subjected to a release treatment on one side, drying the organic solvent, and then molding.

[0180] The shape of the inorganic particle-dispersed molded product is not particularly limited, and may be, for example, in the shape of a sheet.

[0181] Examples of methods for producing the inorganic particle-dispersed molded product include a method of uniformly forming a coating film on a support film by applying the slurry composition using a roll coater, die coater, extrusion coater, curtain coater, or other coating method.

[0182] For example, when the inorganic particle dispersion molded article is in sheet form, the support film used in manufacturing the inorganic particle dispersion molded article is preferably a resin film that is heat-resistant, solvent-resistant, and flexible. The flexibility of the support film allows the inorganic particle dispersion slurry composition to be applied to the surface of the support film using a roll coater, a knife coater, or the like, and the resulting inorganic particle dispersion sheet-forming film can be stored and supplied in a rolled state.

[0183] Examples of the resin forming the support film include polyethylene terephthalate, polyester, polyethylene, polypropylene, polystyrene, polyimide, polyvinyl alcohol, fluorine-containing resins such as polyvinyl chloride and polyvinyl fluoride, nylon, and cellulose.

[0184] The thickness of the support film is preferably, for example, 20 to 100 μm.

[0185] Furthermore, it is preferable to subject the surface of the support film to a release treatment, whereby the support film can be easily peeled off in the transfer step.

[0186] By applying and drying the slurry composition, an inorganic particle-dispersed molded product can be produced.

[0187] Furthermore, by using the slurry composition and the inorganic particle-dispersed molded product as the conductive paste for external electrodes, a multilayer ceramic capacitor as an electronic component can be produced.

[0188] Examples of a method for producing the multilayer ceramic capacitor include a method comprising the steps of printing a conductive paste on the inorganic particle-dispersed molded product and drying the printed conductive paste to produce a dielectric sheet, and laminating the dielectric sheets.

[0189] The conductive paste contains conductive powder.

[0190] The material of the conductive powder is not particularly limited as long as it is conductive, and examples thereof include nickel, palladium, platinum, gold, silver, copper, molybdenum, tin, and alloys thereof. These conductive powders may be used alone or in combination of two or more.

[0191] The method for printing the conductive paste is not particularly limited, and examples thereof include screen printing, die printing, offset printing, gravure printing, and inkjet printing.

[0192] In the method for manufacturing a multilayer ceramic capacitor, dielectric sheets printed with the conductive paste are stacked to produce a raw ceramic laminate, which is then fired in a reducing atmosphere at 1000 to 1500° C. to obtain a plurality of component bodies.

[0193] Next, a conductive paste for external electrodes containing the above-mentioned (meth)acrylic resin particles is applied to both end surfaces of each component blank by a dipping method. Subsequently, it is dried at 100-200°C and then sintered at 450-800°C in a reducing atmosphere to form external electrodes at both ends of the component blank.

[0194] Next, the external electrodes were electroplated to form a Cu film, a Ni film, and a Sn film in this order on the external electrodes, thereby obtaining a multilayer ceramic capacitor.

[0195] Effects of the Invention

[0196] According to the present invention, (meth)acrylic resin particles can be provided that have excellent low-temperature decomposition properties. When used as a binder for dispersing inorganic particles, they can prevent degradation caused by oxidation of inorganic particles such as copper, and can produce an inorganic particle-dispersed slurry composition having particularly excellent dispersibility of fine inorganic particles. Furthermore, (meth)acrylic resin particles can be provided that, particularly when used as a binder for external electrodes of a multilayer ceramic capacitor, can produce a multilayer ceramic capacitor having excellent reliability. Furthermore, methods for producing a carrier composition, a slurry composition, and an electronic component can be provided. DETAILED DESCRIPTION

[0197] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples.

[0198] (Examples 1 to 21, Comparative Examples 1 to 4)

[0199] (Production of (meth)acrylic resin particles)

[0200] A 2 L separable flask equipped with a stirrer, a cooler, a thermometer, a hot water bath, and a nitrogen inlet was prepared. A total of 100 parts by weight of monomers were added to the 2 L separable flask to give the compositions shown in Tables 1 and 2. This was further mixed with 50 parts by weight of butyl acetate as an organic solvent to obtain a monomer mixture.

[0201] In addition, the following monomers were used as monomers.

[0202] MMA: Methyl Methacrylate

[0203] EMA: ethyl methacrylate

[0204] iBMA: isobutyl methacrylate

[0205] 2EHMA: 2-ethylhexyl methacrylate

[0206] The resulting monomer mixture was bubbling with nitrogen for 20 minutes to remove dissolved oxygen, and then the interior of the separable flask was replaced with nitrogen. The mixture was heated to 80° C. in a hot water bath while stirring. A chain transfer agent and a polymerization initiator were then added in the amounts shown in Tables 1 and 2 to initiate polymerization.

[0207] After 7 hours from the start of polymerization, the mixture was cooled to room temperature to terminate the polymerization. The obtained resin solution was then dried in an oven at 130° C. to remove the organic solvent. Thus, (meth)acrylic resin particles were obtained.

[0208] In addition, the following substances were used as a chain transfer agent and a polymerization initiator.

[0209] Chain transfer agent

[0210] CT-1: 3-Mercapto-1,2-propanediol

[0211] CT-2: Mercaptosuccinic acid

[0212] <Polymerization initiator>

[0213] KPS: Potassium persulfate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.)

[0214] VA-086: 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)propionamide] (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.)

[0215] (Preparation of Carrier Composition for Dispersing Inorganic Particles)

[0216] 85 parts by weight of the solvents having the blends shown in Tables 3 and 4 were added to 15 parts by weight of the obtained (meth)acrylic resin particles, and the mixture was stirred until uniform, thereby obtaining a carrier composition for dispersing inorganic particles.

[0217] In addition, the following solvents were used as solvents.

[0218] DHTA: Dihydroterpineol acetate

[0219] BEPG: 2-Butyl-2-ethyl-1,3-propanediol

[0220] (Preparation of Inorganic Particle Dispersion Slurry Composition)

[0221] To the obtained carrier composition for dispersing inorganic particles, a dispersant and inorganic particles were added so as to have the formulations shown in Tables 3 and 4, and the mixture was kneaded with a high-speed stirrer to obtain an inorganic particle-dispersed slurry composition.

[0222] In addition, the following substances were used as a dispersant and inorganic particles.

[0223] Dispersants

[0224] Nopcospar (Japanese: ノプコスパース) 092 (made by Sanyo Chemical Industries, Ltd.)

[0225] <Inorganic particles>

[0226] Copper powder (manufactured by Fujino Metals Co., Ltd., average particle size 0.1 μm)

[0227] Glass frit (manufactured by AGC Corporation, product name ASF-1094, main component Bi2O 3· B2O3· SiO2, average particle size 0.8 μm)

[0228] (Fabrication of multilayer ceramic capacitors)

[0229] First, perovskite-type oxides containing Ba and Ti are used as the main component of the inner-layer and outer-layer ceramic layers as the dielectric material. 80 parts by weight of the above ceramic dielectric powder, 8 parts by weight of an acrylic binder, 10 parts by weight of an organic solvent, 1 part by weight of a plasticizer, and 1 part by weight of a dispersant are mixed to prepare a ceramic slurry. Then, on a resin film, the ceramic slurry is formed so that the dried thickness becomes 3.0 μm to fabricate a green sheet for the inner layer or the outer layer. It should be noted that Marproof MH-03041 (manufactured by NOF Corporation) is used as the acrylic binder, butyl acetate is used as the organic solvent, G-260 (manufactured by Sekisui Chemical Co., Ltd.) is used as the plasticizer, and Nopcospar 092 (manufactured by Sanyo Chemical Industries, Ltd.) is used as the dispersant.

[0230] Next, on the green sheet for the inner layer, a conductive paste is screen-printed in a pattern corresponding to the size of the fired ceramic element (3.2 mm × 1.6 mm) so that the dried thickness becomes 1 ± 0.1 μm.

[0231] It should be noted that as the conductive paste, a conductive paste is fabricated by mixing 50 parts by weight of Ni powder, 5 parts by weight of a perovskite-type oxide containing Ba and Ti as a co-material, 44 parts by weight of the above carrier composition for dispersing inorganic particles, and 1 part by weight of a polycarboxylic acid-based dispersant. It is formulated so that the mixing ratio of the binder resin becomes 6.6 parts by weight / 50 parts by weight of Ni, and the conductive paste is obtained using a ball mill.

[0232] Ni powder with an average particle size of 0.2 μm is used. In addition, a perovskite-type oxide with an average particle size of 30 nm containing Ba and Ti is used.

[0233] Then, after peeling the green sheets for the inner layer and the outer layer screen-printed with the conductive paste from the resin film, a total of 350 sheets are overlapped and crimped to form a laminate, and the laminate is cut into a specified size to be divided into individual unfired ceramic bodies.

[0234] After subjecting each ceramic body to a debinding treatment in a nitrogen atmosphere at 400 °C for 10 hours, it is fired in a nitrogen-hydrogen-water vapor mixed atmosphere under conditions of a maximum temperature of 1200 °C and an oxygen partial pressure of 10 -9 ~10 -10 MPa. [[ID=Next, the inorganic particle-dispersed slurry composition obtained in each of the Examples and Comparative Examples was applied to the fired ceramic body by dipping to a side thickness of 50 μm after drying, and then dried. An electrode layer was then formed in a nitrogen-air-water vapor mixed atmosphere or a nitrogen-hydrogen-water vapor mixed atmosphere at a maximum temperature of 790 to 880°C and an oxygen electromotive force of 220 to 280 mV at the maximum temperature.

[0236] Then, a first plating layer containing Ni was formed on the surface of the electrode layer, and a second plating layer containing Sn was formed on the surface of the first plating layer, thereby forming an external electrode having a three-layer structure, and manufacturing a multilayer ceramic capacitor.

[0237] (Comparative Examples 5 and 6)

[0238] An inorganic particle dispersion carrier composition, an inorganic particle dispersion slurry composition, and a laminated ceramic capacitor were obtained in the same manner as in Example 1, except that polyvinyl butyral resin (BH-3 manufactured by Sekisui Chemical Co., Ltd.) and ethyl cellulose resin (STD-100 manufactured by Nissin Chemicals Co., Ltd.) were used instead of the (meth)acrylic resin particles.

[0239] <Evaluation>

[0240] The (meth)acrylic resin particles and inorganic particle-dispersed slurry compositions obtained in Examples and Comparative Examples were evaluated as follows. The results are shown in Tables 1 to 4.

[0241] (1) Weight concentration of S atoms, weight concentration of OH groups, weight concentration of COOH groups, weight concentration of K atoms

[0242] The weight concentration of S atoms, the weight concentration of OH groups, the weight concentration of COOH groups, and the weight concentration of K atoms contained in the (meth)acrylic resin particles were calculated by the following method.

[0243] Weight concentration of S atoms contained in (meth)acrylic resin particles=[(weight of S atoms contained in all monomers+weight of S atoms contained in all chain transfer agents+weight of S atoms contained in all polymerization initiators) / (weight of all monomers+weight of all chain transfer agents+weight of all polymerization initiators)]×100

[0244] Weight concentration of OH groups contained in (meth)acrylic resin particles=[(weight of OH groups contained in all monomers+weight of OH groups contained in all chain transfer agents+weight of OH groups contained in all polymerization initiators) / (weight of all monomers+weight of all chain transfer agents+weight of all polymerization initiators)]×100

[0245] Weight concentration of COOH groups contained in (meth)acrylic resin particles=[(weight of COOH groups contained in all monomers+weight of COOH groups contained in all chain transfer agents+weight of COOH groups contained in all polymerization initiators) / (weight of all monomers+weight of all chain transfer agents+weight of all polymerization initiators)]×100

[0246] Weight concentration of K atoms contained in (meth)acrylic resin particles=[(weight of K atoms contained in all monomers+weight of K atoms contained in all chain transfer agents+weight of K atoms contained in all polymerization initiators) / (weight of all monomers+weight of all chain transfer agents+weight of all polymerization initiators)]×100

[0247] (2) Particle size

[0248] The obtained carrier composition for dispersing inorganic particles was supplied to a laser diffraction / scattering particle size distribution analyzer (LA-950, manufactured by Horiba, Ltd.) to measure the volume average particle size of the (meth)acrylic resin particles.

[0249] (3) Average molecular weight

[0250] The obtained (meth)acrylic resin particles were measured for polystyrene-equivalent weight average molecular weight (Mw) and number average molecular weight (Mn) by gel permeation chromatography using LF-804 (manufactured by SHOKO Corporation) as a column, and the molecular weight distribution (Mw / Mn) was calculated.

[0251] (4) Viscosity

[0252] The viscosity of the obtained inorganic particle-dispersed slurry composition at 25° C. was measured using a Brookfield viscometer (DVII+Pro, manufactured by Brookfield).

[0253] (5) Storage stability

[0254] The obtained inorganic particle-dispersed slurry composition was stored at a temperature of 23°C and a humidity of 50%. After one month, the state of the slurry composition was checked and evaluated according to the following criteria. If the storage stability is high, it can be said that the dispersibility of the inorganic particles is excellent.

[0255] ○: No separation of the slurry composition or sedimentation of the inorganic particles was observed, and the slurry remained smooth.

[0256] Δ: Sedimentation of the inorganic particles was not observed, but separation of the slurry composition was observed.

[0257] ×: Inorganic particles precipitated or the slurry composition gelled.

[0258] (6) Viscosity stability

[0259] The viscosity of the obtained inorganic particle-dispersed slurry composition at 20°C is defined as the initial viscosity measured in the same manner as in "(4) Viscosity". Furthermore, the measured slurry composition is stored in a constant temperature chamber at 20°C for one month, and the viscosity after storage is measured in the same manner. The rate of change in the viscosity after storage relative to the initial viscosity ([(viscosity after storage - initial viscosity) / initial viscosity] × 100) is determined and evaluated according to the following criteria. If the stability is high, it can be said that the dispersibility of the inorganic particles is excellent.

[0260] ◎: Viscosity change rate is less than 5%.

[0261] ○: The viscosity change rate is 5% or more and less than 10%.

[0262] Δ: The viscosity change rate is 10% or more and less than 20%.

[0263] ×: The viscosity change rate is 20% or more.

[0264] (7) Printability

[0265] The inorganic particle dispersion slurry composition was printed using a screen printer (Micro-Tec, MT-320TV) and a screen plate (Tokyo Process Service, ST500, emulsion 2μm, 2012 pattern, screen frame 320mm×320mm) on a printed glass substrate (soda glass, 150mm×150mm, thickness 1.5mm) at 23°C and 50% humidity. The solvent was then dried in a forced air oven at 100°C for 30 minutes. The printed pattern was observed visually or with a magnifying microscope to confirm the shape of the printed surface edges and evaluated according to the following criteria.

[0266] ⊚: Printing was performed according to the printing pattern, and no tangled threads were observed at the printed edge.

[0267] ○: Printing was performed according to the printing pattern, but one portion with disordered threads at the print end was observed.

[0268] Δ: Printing was performed according to the printing pattern, but 2 to 4 areas with disordered threads at the printed edge were observed.

[0269] ×: Five or more portions were observed where printing was not performed according to the printing pattern or where the printed edges had disordered threads.

[0270] (8) Decomposability

[0271] The resulting inorganic particle-dispersed slurry composition was placed in a platinum pan of a TG-DTA and heated from 30°C in a nitrogen atmosphere at 5°C / min to evaporate the solvent and thermally decompose the resin and dispersant. The time (minutes) required for the degreasing to reach 61.9% by weight (90% by weight degreasing) was then measured.

[0272] (9) Oxidation state

[0273] The resulting inorganic particle-dispersed slurry composition was placed in a platinum pan of a TG-DTA and heated from 30°C in a nitrogen atmosphere at 5°C / min to evaporate the solvent and thermally decompose the resin and dispersant. The time (minutes) required for the degreasing to reach 61.9% by weight (90% by weight degreasing) was then measured.

[0274] Furthermore, the color of the contents of the platinum pan remaining after the measurement was visually evaluated according to the following criteria.

[0275] ○: The color of the content did not change from the color of the copper used for preparing the inorganic particle-dispersed slurry composition.

[0276] ×: The color of the content was changed from the color of copper used for preparing the inorganic particle dispersion slurry composition.

[0277] (10) Withstand voltage failure rate

[0278] The withstand voltage failure rate was calculated by measuring the presence or absence of short-circuit failure when a DC voltage of 150 V was applied to 10,000 of the obtained multilayer ceramic capacitors, and calculating the rate using the following formula.

[0279] Withstand voltage failure rate = number of short-circuited samples / 10,000

[0280] (11) The incidence of electrostatic capacitance reduction products

[0281] Regarding the incidence of products with reduced electrostatic capacitance, the electrostatic capacitance of 10,000 obtained multilayer ceramic capacitors was measured, and samples with less than 90% of the designed capacitance were judged as products with reduced capacitance, and the incidence was calculated.

[0282]

[0283]

[0284]

[0285]

[0286] Industrial applicability

[0287] According to the present invention, it is possible to provide (meth)acrylic resin particles having excellent low-temperature decomposition properties. When used as a binder for dispersing inorganic particles, these particles can prevent degradation caused by oxidation of inorganic particles such as copper, thereby enabling the production of an inorganic particle-dispersed slurry composition having particularly excellent dispersibility of fine inorganic particles. Furthermore, it is possible to provide (meth)acrylic resin particles that, particularly when used as a binder for external electrodes of a multilayer ceramic capacitor, can be used to produce a multilayer ceramic capacitor having excellent reliability. Furthermore, it is possible to provide a carrier composition, a slurry composition, and a method for producing an electronic component.

Claims

1. A (meth)acrylic resin particle having a weight average molecular weight of 100,000 to 1,000,000, The weight concentration of S atoms is 0.03 wt % or more and 2.50 wt % or less.

2. The (meth)acrylic resin particles according to claim 1, wherein The weight concentration of the COOH group is 0.06 wt % or more and 3.00 wt % or less.

3. The (meth)acrylic resin particles according to claim 1 or 2, wherein The weight concentration of K atoms is 0.010 wt % or more and 1.000 wt % or less.

4. The (meth)acrylic resin particles according to any one of claims 1 to 3, wherein The content of the component derived from the acrylic monomer is 5% by weight or less. 5 . The (meth)acrylic resin particles according to claim 1 , wherein the average particle size is 0.1 μm or more and 1.0 μm or less. 6 . A carrier composition comprising the (meth)acrylic resin particles according to claim 1 and a solvent including an organic solvent.

7. The carrier composition according to claim 6, wherein The solvent further contains 100 ppm by weight or more and 40,000 ppm by weight or less of water.

8. The carrier composition according to claim 6 or 7, wherein The organic solvent includes a compound having two or more OH groups. The content of the compound having two or more OH groups in the solvent is 10% by weight or more and 50% by weight or less. 9 . A slurry composition comprising the carrier composition according to claim 6 , inorganic particles, and a dispersant. 10 . A method for producing an electronic component, comprising using the slurry composition according to claim 9 .

Citation Information

Patent Citations

  • Methods for producing ceramic slurry, green sheet and electronic component

    JP2011084433A

  • Conductive paste

    JP2021111525A